Accuracy of Swan‒Ganz catheterization‐based assessment of right ventricular function: Validation study using high‐fidelity micromanometry‐derived values as reference. (18th April 2022) - Shima, Hideki; Nakaya, Toshitaka; Tsujino, Ichizo; Nakamura, Junichi; Sugimoto, Ayako; Sato, Takahiro; Watanabe, Taku; Ohira, Hiroshi; Suzuki, Masaru; Kato, Masaru; Yokota, Isao; Konno, Satoshi
Abstract: Right ventricular (RV) function critically affects the outcomes of patients with pulmonary hypertension (PH). Pressure wave analysis using Swan‒Ganz catheterization (SG‐cath) allows for the calculation of indices of RV function. However, the accuracy of these indices has not been validated. In the present study, we calculated indices of systolic and diastolic RV functions using SG‐cath‐derived pressure recordings in patients with suspected or confirmed PH. We analyzed and validated the accuracies of three RV indices having proven prognostic values, that is, end‐systolic elastance (Ees)/arterial elastance (Ea), β (stiffness constant), and end‐diastolic elastance (Eed), using high‐fidelity micromanometry‐derived data as reference. We analyzed 73 participants who underwent SG‐cath for the diagnosis or evaluation of PH. In this study, Ees/Ea was calculated via the single‐beat pressure method using [1.65 × (mean pulmonary arterial pressure) − 7.79] as end‐systolic pressure. SG‐cath‐derived Ees/Ea, β, and Eed were 0.89 ± 0.69 (mean ± standard deviation), 0.027 ± 0.002, and 0.16 ± 0.02 mmHg/ml, respectively. The mean differences (limits of agreement) between SG‐cath and micromanometry‐derived data were 0.13 (0.99, −0.72), 0.002 (0.020, −0.013), and 0.04 (0.20, −0.12) for Ees/Ea, β, and Eed, respectively. The intraclass correlation coefficients of the indices derived from the two catheterizations were 0.76, 0.71, and 0.57 for Ees/Ea, β, and Eed, respectively. In patients with confirmed or suspected PH, SG‐cath‐derived RV indices, especially Ees/Ea and β, exhibited a good correlation with micromanometry‐derived reference values.